RISK FACTORS OF STUNTING ON CHILDREN AGED 3 – 5 YEARS OLD IN TANAH DATAR DISTRICT 2018 (A FOLLOW-UP STUDY) - Helmizar Helmizar; Resmiati Resmiati (Jurnal Kesehatan Masyarakat Andalas, 2019)
Malnutrition among children under 5 years old has a large impact on cognitive abilities and the risk of degenerative diseases in adulthood. The research aims to know the risk factors of stunting among children 3-5 years old who have intervention in previous research (nutritional supplementation and psychosocial stimulation since age 6–9 months old for 6 months in Tanah Datar District. This research used case control method with 70 samples (35 case: 35 control) taken by total sampling and was analyzed with univariate, bivariate, and multivariate. The result showed that stunting baby based on baby’s birth length was higher in the case group than control group (60% & 34.29% respectively). Good psychosocial stimulation was higher in the control group. Knowledge of nutrition, feeding parenting, health care parenting, cognitive parenting, and exclusive breastfeeding were almost the same in both groups. Likewise with food intake (energy, carbohydrate, fat, protein), except for intake zink, it was higher in the control group than case group. Multivariate analysis showed that psychosocial stimulation parenting influenced the incidence of stunting (p = 0.05) after controlled by baby’s birth length, the age of the children weaned, and Zink intake. It is hoped that parents will carry out good psychosocial parenting, such as the psychosocial stimulation practice who called of manjujai as early as possible in children.